Sosialisasi Penyuluhan Stop Bulying oleh Mahasiswa KKN Universitas Muslim Nusantara Al Washliyah di SD Negeri 102001 Gunung Meriah Kab.Deli Serdang - Annisaul Fadilah; Gladis Pradani; Ika Suriani Pulungan; Muhammad Ariq Ilham; Muhammad Noer Fadlan; Tiflatul Husna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
One of the forms of bullying in school is mocking, telling, molesting, resisting, and even beating. Some people believe that socio-economic variables, physical variations, and past actions are the causes of bullying. Bullying can lower academic achievement, leave school, resign, and even leave school. The purpose of anti-bullying training is to help students avoid actions that may lead to mocking, commanding, molesting, discrimination, and beating. At Mount Meriah State Elementary School 102001, there's an anti-bullying scholarship. For two hours, 75 students participated. re-test and post-test are used to evaluate students' knowledge about bullying.